Gene expression profiling and enrichment functional analyses to compare coronary microvessels and cardiomyocytes in patients with hypertrophic cardiomyopathy. (25th November 2020) - Pisano, A; Le Pera, L; Lombardi, M; Ferre, F; Carletti, R; Cerbelli, B; Lazzeroni, D; Alfieri, O; Foglieni, C; Camici, P; D'Amati, G
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is characterized by severe alterations of cardiac architecture and function involving cardiomyocytes (CM) and coronary microvessels (MV). Coronary microvascular dysfunction, cardiomyocyte hypertrophy and disarray, sarcomeric alterations and interstitial fibrosis are HCM features. The transcriptome profile associated with coronary MV and CM in HCM patients is presently unknown. Purpose: Aim of this study was to improve knowledge of the molecular and biological pahways involved in HCM. To this purpose, the gene expression profile of coronary MV and CM was investigated. Methods: Interventricular septum myectomies from patients with obstructive HCM and donors' hearts (CTR) were collected. Coronary MV (HCM=20, CTR=6) and CM (HCM=10, CTR=5) were laser capture microdissected. RNA-seq was performed by Illumina Nextseq 500, with 76 nt long single-reads. Adapter trimming and quality filtering of the sequenced reads were performed before alignment to the human reference genome. Univocally mapped reads estimated gene expression/sample. Normalized expressed gene levels were quantified. Statistical tests compared HCM and CTR to identify differentially expressed genes (DEG), i.e. up- and down-expressed genes in CM and MV samples. Functional enrichment analysis was performed. Biological categories, i.e. KEGG and Reactome pathways, Gene Ontology terms, protein domains in InterPro database, putative interactors collected in the Intact database and protein annotations in UniProt were considered for inter group comparison of DEGs. Results: Transcriptome analysis identified 392 genes significantly up-regulated and 514 down-regulated in CM samples of HCM vs. CTR, while in MV 681 genes were up-regulated and 815 down-regulated. Although some DEGs were shared between MV and CM (26 and 146 are up- and down-expressed in both sample types), the majority of DEGs displayed a sample-specific pattern. A comparative functional analysis of DEGs highlighted some statistically enriched biological categories including an enrichment of phosphoproteins, with down-expressed genes both in CM (490) and MV (314). Other biological categories annotated as "ubiquitin-like protein conjugation" or "acetylation" in Uniprot database were enriched in down-regulated genes, both in MV and CM. Interestingly, "ribosomal protein" and "ribonucleoprotein" categories resulted as enriched up-regulated DEGs in MV. Conversely, the "citrullination" category was specifically present in annotations associated to down-regulated DEGs in MV from HCM compared to CTR. Conclusions: Our preliminary results support the suitability of RNA-seq analysis to assess: i. the transcriptome profiles and pathways associated to coronary MV and CM; ii. the possible relationship/interplay of MV and CM profiles and HCM disease. The enrichment functional analysis provides preliminary data on candidate DEGs and target proteins for in vitro studies on HCM-related mechanisms. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Ministry of Health